Reservation-based traffic management for autonomous intersection crossing - Myungwhan Choi; Areeya Rubenecia; Hyo Hyun Choi (International Journal of Distributed Sensor Networks)
A scheduling scheme for autonomous intersection crossing is proposed and evaluated. The scheduling scheme determines the flow of autonomous vehicles into an intersection without traffic signals. The objective of the scheduling scheme is to schedule the vehicles’ entrances into the intersection such that there will be no collision among vehicles and the intersection is efficiently utilized. Our scheduling scheme uses reservation-based scheduling approach, and the scheduling is formulated as an optimization problem to find the best sequence of vehicles’ entrances into the intersection. Our scheme is made more practical by allowing the vehicles to move at any speed within a speed range, and it is shown that it is fast enough to be used in real time. Through simulation, it is also shown that our scheduling scheme significantly outperforms the first-come, first-served approach, which is the approach used by other reservation-based scheduling schemes.